Description of seven new species of Edessa Fabricius, 1803 from Central America (Heteroptera, Pentatomidae, Edessinae) - Bitar, Murilo Victor Silva; Mendonça, Maria Thayane Da Silva; Fernandes, José Antônio Marin (Zootaxa, 2023)
Not much is known about the Central American stink bug fauna of the Edessinae subfamily. A recent survey of Costa Rican species from this subfamily listed 65 species, of which 47 were new additions. More recently, a description of a group of species of Edessa added more three species to the fauna of Costa Rica. This work is part of a series of articles aiming to review Edessinae from Central America. In this article seven new species are described from Panama and Costa Rica: Edessa bituberculata sp. n., E. bivenulata sp. n., E. enargocelida sp. n., E. fuscolimbata sp. n., E. fuscopunctata sp. n., E. helvoalata sp. n. and E. holochlorata sp. n.